„Τὸ πνεῦμα καὶ ἡ ψυχὴ καὶ τὸ σῶμα” (1 Tes 5,23): Stoickie źródła rozumienia ducha w Pierwszym Liście do Tesaloniczan = “Τὸ πνεῦμα καὶ ἡ ψυχὴ καὶ τὸ σῶμα” (1 Thess 5:23) : The Stoic Sources of the Understanding of Pneuma in 1 Thessalonians - Pasterczyk, Piotr (Verbum vitae, 2021)
In the article the author interprets 1 Thess 5:23 from the point of view of stoic philosophy. This interpretation claims to answer two questions: Why is St. Paul referring to the tripartite constitution of human being from spirit, soul and body instead of the dualistic constitution of soul and body? What is the exact meaning of the term spirit (πνεῦμα) used in 1 Thess 5:23 as the key term? The usual exegesis understands the term spirit (πνεῦμα) in New Testament as theological description of the Holy Spirit. The interpretation of 1 Thess 5:23 from such a point of view is hardly possibly because it would mean a conflict with the dualistic (Plato, Aristotle) anthropology used by St. Paul in his writings. Moreover it could be interpreted as a pantheistic and monistic explanation of a human being. The proposed answer stems from the interpretation of the term spirit (πνεῦμα) in its philosophical source in stoic philosophy. St. Paul was educated in Hellenistic Tarsus and could have had contact with the stoic thinking taught traditionally in this city. Such an interpretation sufficiently explains the sense of the formula “your whole spirit and soul and body” but it does not mean that St. Paul understood the human being according to a materialistic interpretation of stoic spirit and soul. It means an adoption of the stoic anthropological formula for the expression of the totality of a human being needed in the theological description of the end (παρουσία) in 1 Thessalonians.